200k views
3 votes
5(2x + 7) – 3(x + 5)

User Faide
by
4.9k points

2 Answers

6 votes

☽------------❀-------------☾

Hi there!

~

Simplify the expression.


5(2x + 7) – 3(x + 5)


=


7x + 20

❀Hope this helped you!❀

☽------------❀-------------☾

User Jokin
by
5.1k points
5 votes

Explanation:

let's start with 5(2x+7)

first you need to multiply 5 by 2x which = 10x

then multiple 5 by 7 which =35

That's 10x+35

The second part is -3(x+5)

-3 by x= -3x

-3 by 5= -15

So that becomes -3x-15

Put everything together and it's 10x+35-3x-15

First you do 35-15=20

Then 10x-3x=7x

the answer is 20+7x or 7x+20 (pretty sure it's kind of hard to do this typing out)

User Stevenspiel
by
5.2k points